2000
DOI: 10.1046/j.1440-1819.2000.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation dimension of the human sleep electroencephalogram

Abstract: Sleep electroencephalogram (EEG) was analyzed by nonlinear analysis. Polysomnography of a healthy male subject was analyzed and the correlation dimension was calculated. The mean correlation dimensions decreased from stage 'awake' to stages 1, 2 and 3, and increased during rapid eye movement (REM) sleep. These results were also seen at every sleep cycle. During each sleep cycle the correlation dimensions decreased for slow wave sleep, then increased for REM sleep.The mean correlation dimension of the sleep EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Results by Kobayashi et al (2000) showed successful discrimination of sleep stages by measure of correlation dimension. AVS examined by Jin et al (2002) had decreasing effects on EEG complexity, shown by the first positive Lyapunov exponent as one of nonlinear measures of complexity.…”
Section: Introductionmentioning
confidence: 96%
“…Results by Kobayashi et al (2000) showed successful discrimination of sleep stages by measure of correlation dimension. AVS examined by Jin et al (2002) had decreasing effects on EEG complexity, shown by the first positive Lyapunov exponent as one of nonlinear measures of complexity.…”
Section: Introductionmentioning
confidence: 96%
“…The D2 values of the sleep EEG are influenced by certain parameters [29]. We also investigated the relationships between D2 and the inspective classification over the entire sleep EEG [19]. In those studies, the time lag, Ù, and the number of pairs, N, were changed, and then, the D2 were calculated.…”
Section: Nonlinear Analysismentioning
confidence: 99%
“…D2 decreased from wakefulness to sleep stages 1+2 and 3+4, and increased during REM sleep for a different number of pairs. The D2 of every sleep stage had a tendency to converge to a value when the time lag, Ù, was 40 ms [19]. Since the polysomnogram was scored every 20 s, the time lag was fixed at Ù = 40 ms, based on previous findings and those of empirical studies [19,29].…”
Section: Nonlinear Analysismentioning
confidence: 99%
See 2 more Smart Citations